Análise da interface subjetividade e competências no campo do trabalho - Souza, Susane Petinelli (2006)
This study points out the interface subjectivity and competences in the area of work. Moreover, this study is in search of extending the comprehension about man in this context based on the investigation into conditions of production of discourse competen